2010
DOI: 10.1016/j.cub.2010.08.034
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of the Left Motor Cortex in Learning of a Novel Action Word Lexicon

Abstract: Current theoretical positions assume that action-related word meanings are established by functional connections between perisylvian language areas and the motor cortex (MC) according to Hebb's associative learning principle. To test this assumption, we probed the functional relevance of the left MC for learning of a novel action word vocabulary by disturbing neural plasticity in the MC with transcranial direct current stimulation (tDCS). In combination with tDCS, subjects learned a novel vocabulary of 76 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 40 publications
5
79
1
Order By: Relevance
“…In particular, a flexible pattern of semantic priming has been revealed in the sensorimotor cortex (Grisoni et al, 2016). Third, frontocentral activity emerges in the semantic learning of novel action words (Fargier et al, 2012;James & Swain, 2011;Kiefer, Sim, Liebich, Hauk, & Tanaka, 2007;Liuzzi et al, 2010). Fourth, overt movement or stimulation of these motor areas has a causal effect on simultaneous processing of specific types of action words.…”
mentioning
confidence: 99%
“…In particular, a flexible pattern of semantic priming has been revealed in the sensorimotor cortex (Grisoni et al, 2016). Third, frontocentral activity emerges in the semantic learning of novel action words (Fargier et al, 2012;James & Swain, 2011;Kiefer, Sim, Liebich, Hauk, & Tanaka, 2007;Liuzzi et al, 2010). Fourth, overt movement or stimulation of these motor areas has a causal effect on simultaneous processing of specific types of action words.…”
mentioning
confidence: 99%
“…23 Other studies have also confirmed that the motor cortex has a role in language recovery following aphasia. 12,24 In this context, we hypothesized that motor cortex modulation would be an interesting target for language recovery treatment. We chose the unaffected motor cortex, based on previous experience showing that this is an effective target for enhancing motor recovery in stroke cases.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the primary motor cortex to language has been shown by neuroimaging studies, 12 and previous studies showing that modulation of the unaffected motor cortex is an advantageous strategy for decreasing imbalanced interhemispheric activity in stroke cases. 13,14 Based on these data, our aim was to conduct a preliminary open-label study to assess the effects from modulating plasticity by means of excitability-diminishing cathodal transcranial direct current stimulation over the unaffected primary motor cortex, in order to obtain preliminary efficacy and safety data on its effects on language.…”
Section: 11mentioning
confidence: 91%
“…To date, many studies of cognition combined offline rTMS, TDCS, or TACS with various functional brain mapping techniques. Functional magnetic resonance imaging (fMRI) (Andoh and Paus, 2011;Andoh and Zatorre, 2013;Liuzzi et al, 2010), electroencephalography (EEG) (Bergmann et al, 2008;De Gennaro et al, 2008;Huber et al, 2007), or, more recently, magnetoencephalography (MEG) (Marshall et al, 2015;Zwanzger et al, 2014) has been successfully used after a conditioning NTBS session to delineate stimulation-induced changes in neural activity on the network level (see Section 3).…”
Section: Offline Transcranial Stimulationmentioning
confidence: 99%